PENGARUH SUSTAINABILITY REPORTING TERHADAP FIRM VALUE DENGAN KAPITALISASI PASAR SEBAGAI PEMODERASI (Studi pada Perusahaan dalam Indeks IDX SRI-Kehati yang Menerbitkan Sustainability Report pada Tahun 2017-2021) - Axel Ramadhani Liemawan Pranoto; Marsono Marsono (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of sustainability reporting on the firm value of companies listed on the IDX SRI-Kehati index and to analyze that market capitalization moderates the relationship between sustainability report disclosure and firm value. This research is an explanatory research with a case study approach with 25 companies registered as a population. A total of 14 companies were selected using purposive sampling. Data from 2017 to 2021 is obtained from secondary sources. Simple linear regression analysis is used as a tool to analyze disclosures in sustainability reports on firm value. The residual test is used to determine the effect of market capitalization as a moderating variable between sustainability reporting and firm value. This study found that the sustainability reporting variable has no significant effect on firm value and market capitalization is not a moderator between the sustainability reporting variable and firm value variable. Therefore, this study recommends that management intensify efforts to ensure maximum compliance with the GRI sustainability reporting guidelines to reflect their firm value. Investors should also consider the sustainability reporting index in making investment decisions because it provides investors with information beyond financial numbers.